Pengaruh Pemanfaatan Dana KIP Kuliah terhadap Pemenuhan Kebutuhan Penunjang Akademik Mahasiswa Universitas Teknologi Sumbawa - Niken Widatiningsih; Sriyatun Sriyatun (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of KIP Kuliah fund utilization on the fulfillment of academic support needs among students at Sumbawa University of Technology. A quantitative, causal-associative survey design was employed. The population consisted of 459 active KIP Kuliah recipients, from which 214 respondents were selected using the Slovin formula and purposive sampling. Primary data were collected through a five-point Likert-scale questionnaire and analyzed using IBM SPSS Statistics version 32. The analytical procedures included instrument validity and reliability testing, normality, heteroscedasticity and linearity tests, simple linear regression, a partial t-test, and the coefficient of determination. The findings show that the research instruments were valid and reliable, the residuals were normally distributed, and the model met the heteroscedasticity and linearity assumptions. The regression equation was Y = 25.518 + 0.063X. KIP Kuliah fund utilization did not have a statistically significant effect on the fulfillment of students' academic support needs (t = 1.302; p = 0.194). The coefficient of determination was 0.008, indicating that fund utilization explained only 0.8% of the variation in academic support needs. These results imply that KIP Kuliah funds are used for both academic and daily living expenses, while the fulfillment of academic support needs is more strongly associated with other factors outside the model.